Anemia, a moderate public health concern among adolescents in South Ethiopia. - Mohammed Feyisso Shaka; Yohannes Addisu Wondimagegne (PLoS ONE)
Background Adolescence is characterized by rapid growth and development and iron requirements increase during this time. Adolescents with poor diet in early childhood and/or females with an early onset of menarche may be at greater risk for developing anemia due to the rapid depletion of iron stores in their bodies. Objective The objective of this study was to assess the prevalence and severity of anemia among school adolescents in Wonago district, Gedeo Zone, South Ethiopia. Methods A school based cross-sectional study was conducted among 443 randomly selected school adolescents across 15 schools (2 secondary schools and 13 primary schools) in the district. Hemoglobin concentration from a capillary blood sample was determined by portable hemoglobin meter (HemoCue). Descriptive statistics were computed for prevalence of anemia, anthropometric measurements, socio-economic and socio-demographic variables. A hierarchical multivariable logistic regression analysis was done to identify determinants of anemia among adolescents. Results The prevalence of anemia among adolescents in the study area was 22%. Anemia was higher among those in early adolescence period (10-13 years) (AOR: 4.75, CI: 1.69-13.35) compared to late adolescence (17-19 years) and among those with height for age z-score less than -2 (AOR: 6.23, CI: 1.98-19.62). Similarly, anemia was higher among those in households with a family size greater than five members (AOR: 9.82, CI: 2.42-39.88), adolescents from rural areas (AOR: 4.37, CI: 1.54-12.46) and families who purchase food needed for daily consumption (AOR: 3.25, CI: 1.42-7.45). On the other hand, adolescents from middle wealth quintiles (AOR: 0.26 (CI: 0.07-0.98)) and female adolescents (AOR: 0.34 (CI: 0.15-0.79) were less likely to be anemic in this study. Conclusions The prevalence of anemia in this population is of moderate public health concern, adolescents of both sexes are among groups at risk for the development of anemia. The need for further assessment of the etiology of anemia should be considered to design pragmatic intervention programs.